Duplex and quadruplex DNA binding and photocleavage by trioxatriangulenium ion. - Pothukuchy, A; Mazzitelli, C; Rodriguez, M; Tuesuwan, B; Salazar, M; Brodbelt, J; Kerwin, S (2005)
The stable trioxatriangulenium ion (TOTA) has previously been shown to bind to and photooxidize duplex DNA, leading to cleavage at G residues, particularly 5'-GG-3' repeats. Telomeric DNA consists of G-rich sequences that may exist in either duplex or G-quadruplex forms. We have employed electrospray ionization mass spectrometry (ESI-MS) to investigate the interactions between TOTA and duplex DNA or G-quadruplex DNA. A variety of duplex decamer oligodeoxynucleotides form complexes with TOTA that can be detected by ESI-MS, and the stoichiometry and fragmentation patterns observed are commensurate with an intercalative binding mode. TOTA also forms complexes with four-stranded and hairpin-dimer G-quadruplex oligodeoxynucleotides that can be detected by ESI-MS. Both the stoichiometry and the fragmentation patterns observed by ESI-MS are different than those observed for G-tetrad end-stacking binding ligands. We have carried out (1)H NMR titrations of a four-stranded G-quadruplex in the presence of TOTA. Addition of up to 1 equiv of TOTA is accompanied by pronounced upfield shifts of the G-tetrad imino proton resonances in the NMR, which is similar to the effect observed for G-tetrad end-stacking ligands. At higher ratios of added TOTA, there is evidence for additional binding modes. Duplex DNA containing either human telomeric repeats (T(2)AG(3))(4) or the Tetrahymena telomeric repeats (T(2)G(4))(4) are readily photooxidized by TOTA, the major sites of oxidation being the central guanine residues in each telomeric repeat. These telomeric repeats were incorporated into duplex/quadruplex chimeras in which the repeats adopt a G-quadruplex structure. Analysis by denaturing polyacrylamide gel electrophoresis reveals significantly less TOTA photocleavage of these quadruplex telomeric repeats when compared to the duplex repeats.